Changing dynamics in the spread and management of banana Xanthomonas wilt disease in Uganda over two decades - Kubiriba, Jerome; Erima, Rockefeller; Tugume, Arthur K.; Tinzaara, William; Tushemereirwe, Wilberforce K. (American Phytopathological Society, 2023)
Banana Xanthomonas wilt (BXW) is a destructive disease caused by Xanthomonas vasicola pv. musacearum (Xvm) bacterium that indiscriminately infects all banana varieties grown in East and Central Africa (ECA). In this region, BXW was first reported in 2001 in Uganda and was projected to eliminate >90% of Uganda’s bananas worth US$4 billion if not controlled in less than 10 years. Lack of basic information led to application of control approaches that were based on similarity of BXW symptoms to those of Moko disease of bananas. The approaches were however, unsuccessful and in 7-9 years, BXW had covered six countries and threatened to wipe out the banana industry in ECA. However, BXW has to-date been tamed, mainly due to relentless and systematic deployment of carefully crafted and packaged cultural control practices based on epidemiological information generated within target banana cropping ecosystems. In Uganda, the initial “top-down” communication approaches reached >85% banana farming communities but did not mobilize the communities enough into action; hence, only 30% impact in controlling BXW was registered. In contrast, participatory approaches mobilised farming communities into action and effectively controlled BXW at field and community levels to near eradication. The approaches effectively controlled BXW in Uganda, and consequently, in eastern Kenya, northern Tanzania, Rwanda, Burundi and DRC. This paper reviews step-wise processes leading to success over the 2 decades and identifies critical research gaps. Deployment of resistant genotypes is urgently needed as a significant addition to the BXW management tool-box to create BXW-free banana cropping systems in ECA.